Pengaruh Honor terhadap Peningkatan Kinerja Guru di YPI Al Amanah Cibinong - Bogor - Muhammad Aliyudin; Dedi Junaedi; Agung Prasetyo (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2021)
The background of this research is that there are still teachers who show low performance. The problems that have been identified include teacher honorarium allowances. Therefore the aim of this study was to determine the effect of teacher honorarium allowances on improving teacher performance at the Al Amanah Islamic Education Foundation, Cibinong, Bogor. The research method used is a quantitative method. The data collection technique used a questionnaire. The data analysis technique uses descriptive analysis, quantitative analysis and hypothesis testing. The results showed Teacher honorarium allowances (variable X) have a significant contribution and have a very high effect and the direction of a positive relationship to the variable increasing teacher performance at the Al Amanah Education Foundation, Cibinong, Bogor is 74.5% and 25.5% increase in teacher performance is influenced by other factors.